DETERMINANTS OF FINANCIAL PLANNING: A META-ANALYSIS ON THE EFFECTS OF FINANCIAL LITERACY AND INCOME - Daffa Eka Septianda; Clarashinta Canggih (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This meta-analytic study aims to synthesize empirical evidence on the influence of financial literacy and income on financial planning, addressing inconsistent findings in previous literature. Design/Methodology/Approach: Employing a quantitative meta-analysis approach following PRISMA guidelines, this study analyzed secondary data from primary empirical studies published between 2021 and 2026. A systematic search across Scopus and Google Scholar yielded k = 11 eligible studies. A random-effects model was applied to account for expected methodological and demographic heterogeneity. Findings: The pooled effect sizes indicate that both financial literacy (r = 0.460, p = .065) and income level (r = 0.452, p = .268) show moderate effect sizes but do not reach statistical significance. Significant heterogeneity was observed in both analyses (Financial Literacy: Q(6) = 50.91, p < .001; Income: Q(3) = 38.75, p < .001), suggesting the presence of potential moderating variables. Novelty: This study provides a novel behavioral finance perspective by explaining the